E-service quality and promotion on customer loyalty: The importance of customer satisfaction - Sukardi Sukardi; Md. Abu Jahid; Suryana Hendrawan (Jurnal Fokus Manajemen Bisnis, 2023)
Satisfaction and loyalty are two important things that must be maintained in a business. Various factors, including service quality and promotion, can also influence these. Bank services have entered a new digital phase. Bank services have implemented e-service as part of non-personal services that can be done anywhere and anytime, especially in an effort to deal with customer financial problems. This study intends to ascertain the impact of customer satisfaction, e-service quality, and promotion on customer loyalty as well as the impact of e-service and promotion on customer satisfaction. 173 respondents made up the study's sample, which was selected using a purposive sampling technique and non-probability sampling. Smart PLS is then used to process the data that was obtained. The outcomes demonstrated a negative correlation between customer satisfaction and e-service quality and promotion. The amount of customer loyalty has also been proven to be negatively impacted by the quality and promotion of e-service. The degree of customer pleasure, which has been shown to have a favorable impact on customer loyalty, also signals varied outcomes.